Modelagem termodinâmica de gás de síntese de combustível derivado de resíduos sólidos urbanos com simulações em ciclos de potência a gás e vapor - Monteiro, Vitor Alberto Lemes (2019)
Faced with the increasing generation of municipal solid waste, approximately 440 kg per person annually, the commonly techniques employed for its management face serious problems related to disposing areas, contamination and economic loss. Gasification is a waste to energy technology, which converts biomass into synthesis gas by heating under controlled conditions, is very promising to meet the demands of population growth and, consequently, municipal solid waste production. Thereby, the present work aimed to develop the thermodynamic modeling of synthesis gas from gasification of refuse derived fuel from municipal solid waste and to perform simulations in gas and steam power cycles used in power plants. Chemical stoichiometry calculations due to its combustion were conducted to obtain parameters required to power cycle simulation. It was concluded that the species CO, CH4, C2H4 and H2, besides the higher carbon chain present in the synthesis gas in small quantities, had significant influence on the parameters such as lower heating value, gas density and adiabatic flame temperature. The application of synthesis gas in power cycles involving internal combustion has high complexity and makes the use of Brayton and Otto cycles unfeasible in Gasification Power Plants. The Gas-Steam Combined Cycle presented the higher efficiency in energy conversion, however involves more machines and equipment costs. Thus, the most suitable option for that application of synthesis gas was the Regenerative Rankine Cycle.